2013
DOI: 10.1021/es304238v
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom up Approach to on-Road CO2 Emissions Estimates: Improved Spatial Accuracy and Applications for Regional Planning

Abstract: On-road transportation is responsible for 28% of all U.S. fossil-fuel CO2 emissions. Mapping vehicle emissions at regional scales is challenging due to data limitations. Existing emission inventories use spatial proxies such as population and road density to downscale national or state-level data. Such procedures introduce errors where the proxy variables and actual emissions are weakly correlated, and limit analysis of the relationship between emissions and demographic trends at local scales. We develop an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…Uncertainty in the magnitude of on-road emissions at the national level is estimated to be on the order of 3-5% for developed countries (4,35), but at subnational or state scales, existing inventories disagree by as much as 40% (3), and at city scales, uncertainty can be as large as 50-100% (13). Direct quantification of the uncertainty in US on-road emissions is made impossible by the absence of independent data sources against which to compare government estimates (4).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Uncertainty in the magnitude of on-road emissions at the national level is estimated to be on the order of 3-5% for developed countries (4,35), but at subnational or state scales, existing inventories disagree by as much as 40% (3), and at city scales, uncertainty can be as large as 50-100% (13). Direct quantification of the uncertainty in US on-road emissions is made impossible by the absence of independent data sources against which to compare government estimates (4).…”
Section: Significancementioning
confidence: 99%
“…Nationally, the on-road sector represented 28% of total fossil fuel CO 2 emissions in 2012 and is responsible for almost half of the growth in total US emissions since 1990 (2). Despite being a substantial component of US emissions, on-road CO 2 remains poorly quantified at substate and urban scales (3)(4)(5). Reducing the uncertainty of on-road CO 2 emissions at finer spatial scales is critical to understanding the determinants of motor vehicle emissions (3), constraining carbon budgets (4), and supporting greenhouse gas (GHG) emission monitoring and abatement verification (5), particularly at the scale of cities, which have emerged as hubs of climate change mitigation activity (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These factors contributed 374 to the decommissioning of TAO in January 2016. The poor performance of our model system when 375 using the EDGAR v4.2 inventory to simulate CO2 mixing ratios was also found by a study quantifying 376 on-road CO2 emissions in Massachusetts, USA (Gately et al, 2013). In this study, EDGAR emission 377 estimates were found to be significantly larger than any other inventory by as much as 9.3 million 378 tons, or >33 %.…”
Section: Preliminary Analyses Using the Soce Ffdas V2 And Edgar V42mentioning
confidence: 67%